Perlindungan Konsumen Muslim atas Produk Halal - Bambang Sugeng Ariadi Subagyono; Trisadini Prasastinah Usanti; Zahry Vandawati Chumaida; Fiska Silvia; Indira Retno Aryatie (Perspektif Hukum, 2020)
Every religious adherent is guaranteed to choose and practice his religion, so the state is obliged to provide protection and guarantee regarding the halalness of the products used and used by the community. Whereas in society there are still many conclusions about various products that have not been guaranteed their halalness and regulations have not provided legal certainty and guarantees for Muslim communities. So to provide legal certainty the promulgation of Law number 33 of 2014 concerning Halal Product Guarantee. The guarantee for the implementation of Halal Products is aimed at providing comfort, safety, and certainty of information on Halal Products for the public in consuming and using Products, as well as increasing added value for Business Actors to produce and sell Halal Products. The halal certificate must be submitted by the business actor in writing to BPJPH while the determination of the halalness of the product is still carried out by MUI through the Halal Fatwa Session. This research is a normative legal research that uses a statute approach and a conceptual approach.